2014
DOI: 10.1002/chem.201302053
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Interconversions: Unique 100 % Reversible Transformations between the Ground and Metastable States in Single‐Crystals of a Series of Nickel(II) Nitro Complexes

Abstract: The solid-state, low-temperature linkage isomerism in a series of five square planar group 10 phosphino nitro complexes have been investigated by a combination of photocrystallographic experiments, Raman spectroscopy and computer modelling. The factors influencing the reversible solid-state interconversion between the nitro and nitrito structural isomers have also been investigated, providing insight into the dynamics of this process. The cis-[Ni(dcpe)(NO2)2] (1) and cis-[Ni(dppe)(NO2)2] (2) complexes show rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 52 publications
5
51
1
Order By: Relevance
“…The reaction pathway is similar to that proposed by Warren et al for the [Ni(dppe)Cl(NO 2 )] → [Ni(dppe)Cl(ΟNO)] linkage isomerization process. In the linkage isomerization [Ni( κN1‐NO 2 )(S 2 CNHMe)(PMe 3 )] [Ni( κnormalO,O2‐ONO)(S 2 CNHMe)(PMe 3 )] pathway the starting point is the singlet ground state ( GS ) of the [Ni( κN1‐NO 2 )(S 2 CNHMe)(PMe 3 )] complex, which on irradiation is transformed to the triplet excited state ( GS* ) with an energy demand of 10.1 and 7.6 kcal/mol in vacuum and solution, respectively.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The reaction pathway is similar to that proposed by Warren et al for the [Ni(dppe)Cl(NO 2 )] → [Ni(dppe)Cl(ΟNO)] linkage isomerization process. In the linkage isomerization [Ni( κN1‐NO 2 )(S 2 CNHMe)(PMe 3 )] [Ni( κnormalO,O2‐ONO)(S 2 CNHMe)(PMe 3 )] pathway the starting point is the singlet ground state ( GS ) of the [Ni( κN1‐NO 2 )(S 2 CNHMe)(PMe 3 )] complex, which on irradiation is transformed to the triplet excited state ( GS* ) with an energy demand of 10.1 and 7.6 kcal/mol in vacuum and solution, respectively.…”
Section: Resultssupporting
confidence: 82%
“…Recently Warren et al reported on the synthesis and characterization of a series of square planar group 10 metal complexes that exhibit switchable metastable‐state behavior The solid‐state, low‐temperature linkage isomerism in these complexes have been investigated by a combination of photocrystallographic experiments, Raman spectroscopy and computer modeling. The mechanism of the interconversion has been investigated by theoretical calculations based on the model complex [NiCl(dppe)(NO 2 )] (dppe = 1,2‐bis(diphenylphosphino)ethane).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include diarylethenes [17] and naphthalocyanine [53]. Linkage isomers are an interesting class of coordination complexes, which have one (or more) ligands with switchable connectivity to the metal ion [54]. In all of the above cases, the two states of the molecule correspond to local minima in the ground-state potential energy surface.…”
Section: Actuators Using Molecular Switchesmentioning
confidence: 98%
“…[3,4] But in both cases it can affect the reactionp ath, andl imits the number of intermediates so that only selective reactions may occur in solids. [7][8][9][10][11] and medium sized [6,[12][13][14][15] ligands, or even solid-state trans-cis (diag-lat)i somerization of some Re, W, and Mo complexes [16][17][18] and the E/Z photoisomerization of aZ nc omplex. [5] Typically,a tomic movement in the course of a solid-state chemical reaction is accompanied with degradation of am aterial, and inspection of such reactions in situ by means of diffraction techniques is challenging.…”
Section: Introductionmentioning
confidence: 99%